CCL5 promotes LFA-1 expression in Th17 cells and induces LCK and ZAP70 activation in a mouse model of Parkinson’s disease - Zhao, Jingwei; An, Ke; Mao, Zhijuan; Qu, Yi; Wang, Danlei; Li, Jiangting; Min, Zhe; Xue, Zheng (Frontiers in Aging Neuroscience, 2023)
Background: Parkinson's disease (PD), which is associated to autoimmune disorders, is characterized by the pathological deposition of alpha-synuclein (α-Syn) and loss of dopaminergic (DA) neurons. Th17 cells are thought to be responsible for the direct loss of DA neurons. C-C chemokine ligand 5 (CCL5) specifically induces Th17 cell infiltration into the SN. However, the specific effect of CCL5 on Th17 cells in PD and the relationship between CCL5 and lymphocyte function-associated antigen-1 (LFA-1) expression in Th17 cells are unknown.We evaluated the effects of CCL5 on LFA-1 expression in Th17 cells in mice treated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and examined Th17 cell differentiation upon CCL5 stimulation in vitro. Furthermore, we assessed the effects of CCL5 on tyrosine kinase zeta-chain-associated protein kinase 70 (ZAP70) and lymphocyte-specific protein tyrosine kinase (LCK) activity in CCL5-stimulated Th17 cells in vivo and in vitro.: CCL5 increased the proportion of peripheral Th17 cells in MPTP-treated mice, LFA-1 expression on Th17 cells, and Th17 cell levels in the SN of MPTP-treated mice. CCL5 promoted Th17 cell differentiation and LFA-1 expression in naive T cells in vitro. Moreover, CCL5 increased Th17 cell differentiation and LFA-1 expression by stimulating LCK and ZAP70 activation in naive CD4 + T cells. Inhibiting LCK and ZAP70 activation reduced the proportion of peripheral Th17 cells and LFA-1 surface expression in MPTP-treated mice, and Th17 cell levels in the SN also significantly decreased. Conclusion: CCL5, which increased Th17 cell differentiation and LFA-1 protein expression by activating LCK and ZAP70, could increase the Th17 cell number in the SN, induce DA neuron death and aggravate PD.